Leveraging Literacies Through Collaborative, Source‐Based Planning and Teaching in Social Studies and Language Arts. Issue 5 (31st October 2017) - Patterson, Nancy; Weaver, Joanna; Fletcher, Jamie; Connor, Bryce; Thomas, Angela; Ross, Cindy
Abstract: The value of preparing students for college, careers, and civic life is a shared outcome of social studies and language arts teachers. This study explores how developing content and civic literacy to these ends can be fortified through language arts and social studies teacher collaboration in source‐based planning and teaching. Although numerous studies of the positive impacts of coplanning have been conducted, there has been less focus on the actual implementation of the teachers' collaborative plans and teachers' perceptions of their impact. Through examination of teachers' plans and follow‐up interviews about implementation, researchers found that teachers both planned and implemented inquiry‐based, collaborative plans using sources to promote various types of literacy and that the collaboration increased student interest and inquiry in social studies and integrated language arts. Teachers' perceptions of the impacts of the collaboration on students' literacy skills were positive.